(N{ALQPIN I gORKIJ(B.s (NiSTORIQ WZAIMOOTNO[ENIJ W KONTEKSTE OB]ESTWENNOGO I LITERATURNO(B- (NHUDOVESTWENNOGO PROCESSA KONCA (BXIX-(NPERWOJ TRETI (BXX (NWEKA(B.s - (Nw(B.(NdMITRIEWSKIJ(B.s ((NmOSKWAs (NmUZYKAs, 1981)
(NiMENA fEDORA iWANOWI^A {ALQPINA I aLEKSAQ mAKSIMOWI^A gORXKOGO OKRUVENY LEGENDAMI(B.s
Keywords: (NMONOGRAFIQs